A corpus-based investigation of the interlanguage of university students in East Malaysia / Lilly Metom ... [et al.] - Metom, Lilly; Hakim, Simon Botley @ Faizal (2011)
This report describes the culmination of the learner corpus project called CALES (Corpus-based Archive of Learner English in Sarawak). The original two phases of the project collected 356,000 words of learner writing in the form of argumentative essavs written by students taking English proficiency courses in *UiTM's Sarawak Branch Campus (Botley et al, 2005, 2007), This new project has increased this total to over 480,000 words of digital text and has collected more essays from four different institutions in order to further expand and enrich the corpus.